EVALUASI EFEKTIFITAS PENGGUNAAN MEDIA DALAM MENURUNKAN PREVALENSI TUBERKULOSIS DI BALAI PEMBERANTASAN DAN PENCEGAHAN PENYAKIT PARU PAMEKASAN - qurrotu aini (NHM PRESS, 2018)
Pulmonary tuberculosis is still a serious health problem that needs to be equipped with appropriate countermeasures and accurate. The increase in cases and deaths caused by pulmonary tuberculosis, among others, because it is not threated any of them do not understand have been infected with the TB bacillus so that the prevalence of tuberculosis is still quite high. Therefore, the necessary handling seriously through health education role that communication education with intensive use of media that will reduce the prevalence or at least remain. In general. The purpose of the study to evaluate the effectivesness oh the use of media in reducing the prevalence of tuberculosis. The study “evaluation of Effectiveness of Media in Reducing Prevalence Of Tuberculosis in The Central Eradication and Prevention of Lung Disease Pamekasan “ use purposive sampling with the snowball method. Sample research is pulmonary tuberculosis patients treated in BP4 much as 3 respondents. The results showed three informants as respondents are all in the first 2 months visiting tuberculosis drug taking as much as 8 times visit support the availability of infrastructure, knowledge of personel. Strategy, advocacy, resoueces and funding are two inhibiting factors lack of education and knowledge of the patients, the lack of commitment oh health workers all of the prevalence of tuberculosis as well as visual media is the most effective in reducing the prevalence of tuberculosis. Sugestions for researchers to address the increasing prevalence of lung integration across every sector and cross-sectoral programs to develop internal networks and external networks.